The Effect of Competency and Creativity Programs on Employee Performance at The Mayor's Office of The Malang City Personnel and Human Resource Development Agency (Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Malang) - Deviyanti; Nur Ida Iriani; Setyaningrum, Fitria (International Journal of Management and Business, 2025)
The provision of competency programs and the existence of work creativity play an important role in improving employee performance. The purpose of this study is to determine the influence of competency and creativity development programs on employee performance at the Mayor's Office of the Malang City Personnel and Human Resources Development Agency partially and simultaneously. This study uses a quantitative method. The research population is 45 employees. The determination of the sample of this study uses the purposive sampling method so that a research sample of 44 employees was obtained. The data collection technique uses a questionnaire. The data analysis method used is multiple linear regression using the SPSS version 25 program. The results of the study prove that partially, the competency program has a significant effect on employee performance with a t-value of 4.824 and creativity has a significant effect on employee performance with a t-value of 4.305. The results of the simultaneous (together) competency and creativity programs have a significant effect on employee performance at the Mayor's Office of the Malang City Personnel and Human Resources Development Agency with an F value of 37.805 or an influence of 64.8%. The results of this study can be understood that the existence of work competency and creativity programs is able to improve employee performance.